Maximizing Agency Theory in Integrated Reporting of Companies Listed in Kompas100 Index - Widhiastuti, Ratieh; Harto, Puji (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2022)
This study aimed to examine the effect of the audit committee, independent commissioners and stakeholder pressure on integrated reporting either directly or moderated by profitability. The object of research was companies listed in Kompas100 index for three consecutive years from 2018-2020. The research sample was determined by using purposive sampling method, and obtained 231 units of analysis. The analysis tool used descriptive and moderated regression analysis. The results of the descriptive analysis showed that on average the number of audit committees and independent commissioners was ideal and according to the rules, institutional ownership was more than 50% of all companies in all industrial sectors. The test results showed that the audit committee and stakeholder pressure had a significant positive effect on integrated reporting, while the independent commissioner had a significant negative effect. Profitability was able to weaken the effect of the audit committee, strengthen the effect of independent commissioners, and was not able to moderate the effect of stakeholder pressure on integrated reporting. Suggestions from this study are to increase the number of audit committees and independent commissioners for the company indexed Kompas100 that does not meet the minimum standards, as a form of corporate responsibility and a form of company compliance with OJK rules.